Lung deposition of inhaled once-daily long-acting muscarinic antagonists standard jet nebulizer or dry powder inhaler, measured using functional respiratory imaging, in patients with chronic obstructive pulmonary disease - Glenn D. Crater; Karmon Johnson; Jonathan Ward; Jan De Backer (Therapeutic Advances in Respiratory Disease, 2022)
Background: Data for bronchodilator deposition via nebulizers and dry powder inhalers (DPIs) in the respiratory tract of patients with chronic obstructive pulmonary disease (COPD) are limited. We used functional respiratory imaging (FRI) to determine deposition patterns for revefenacin solution via a PARI LC ® Sprint ® nebulizer and tiotropium powder via HandiHaler ® DPI. Methods: Ten patients with COPD, of whom 9 had severe airflow obstruction, were selected from FLUIDDA’s database. The study did not enroll patients. Drug deposition in the extrathoracic and intrathoracic regions, including the central and peripheral airways was simulated by FRI. The percentage of delivered dose and central-to-peripheral (C/P) deposition ratio for nebulizer and DPI were evaluated. Results: Mean ± standard deviation (SD) age was 64.7 ± 7.1 years, height was 168.8 ± 8.5 cm, and percent predicted forced expiratory volume in 1 s was 40.8 ± 12.3%; 50% of patients were men. At optimal inhalation flow, intrathoracic and peripheral deposition was three-fold higher for revefenacin via nebulizer than tiotropium via HandiHaler (mean ± SD 34.6 ± 8.53% versus 10.9 ± 5.67% and 18.2 ± 4.30% versus 5.8 ± 2.73% of delivered dose, respectively). Similar results were observed for suboptimal flow (mean ± SD percentage of revefenacin versus tiotropium: intrathoracic, 32.1 ± 8.3% versus 15.1 ± 5.9%; peripheral; 16.6 ± 4.1% versus 8.4 ± 2.9%). The C/P deposition ratio for nebulizer was similar to DPI (mean ± SD 0.915 ± 0.241 versus 0.812 ± 0.249 at optimal; 0.947 ± 0.253 versus 0.784 ± 0.219 at suboptimal flow), even though the mass median aerodynamic diameter of revefenacin was higher than tiotropium. C/P deposition ratio for revefenacin decreased after bronchodilation (0.915 ± 0.241 pre-bronchodilation versus 0.799 ± 0.192 post-bronchodilation), suggesting progressively better deposition in the peripheral region, assuming bronchodilation occurred during the nebulization process. Conclusions: These results demonstrate more efficient intrathoracic and peripheral deposition for revefenacin via standard jet nebulizer than tiotropium via HandiHaler, with similar C/P deposition ratio in patients with COPD. Nebulizers are an efficient alternative to DPIs for bronchodilator administration in patients with COPD.